Public Consultation in Environmental Assessments 1997-2000 : Findings from the Third Environmental Assessment Review - Rukuba-Ngaiza, Nightingale; Lubis, Rusdian; Cullen, Michelle; Zongmin Li; Mausolff, Christopher (World Bank, Washington, DC, 2014)
According to internal and external reviews of the public consultation process, public consultations have increasingly become a standard part of the environmental assessment process in Bank operations. However, the current challenge for Bank operations focuses on the quality of public consultations and the extent to which they influence project design and effect project impact. In an attempt to evaluate how projects were meeting this challenge, the Third Review assessed whether qualitative and quantitative improvements in EA public consultations had taken place for Category A and B Bank-financed projects (A project is classified as Category A if it is "likely to have significant adverse environmental impacts that are sensitive, diverse or unprecedented." On the other hand, a project is classified as Category B if it will not have significantly adverse impacts on human populations or environmentally important areas including wetlands, forests, grasslands, and other natural habitats.) In order to provide guidance for improving public consultation in future EA processes, the review also identified challenges and best practices, and briefly examined whether these improvements were similarly reflected in the work of financial intermediaries and regional and sectoral environmental assessments (SEAs).